Verb concatenation in Kachin - Matisoff, James A. (2024)
During the summer of 1963, after my first year as a graduate student in the Berkeley linguistics department, it was my good for¬tune to work for several months with LaRaw Maran, then a graduate student in an hropology at the University of Arizona, on a grammatical analysis of the Kachin language (now usually called Jinghpaw or Jingpho), which is his native tongue. LaRaw, now a professor of linguistics a the University of Indiana, was, technically speaking, my "informant', as I attempted to put into practice for the first time the principles of field linguistics I was absorbing from my teachers.